The influence of lower-limb strength and power on the speed and heat results of professional Brazilian surfers - Souza, P. C.; Guerra, R. L. F. (International Journal of Sports Physiology and Performance, 2025)
Purpose To correlate speed and heat scores with anthropometric variables and lower-limb strength and power in professional surfers.